Microstructure development during explosive welding of metal foil：morphologies, mechanical behaviors and mechanisms - Yang, Ming; Xu, Junfeng; Ma, Honghao; Lei, Mingzhun; Ni, Xiaojun; Shen, Zhaowu; Zhang, Bingyuan; Tian, Jie (Composites. Part B, Engineering, 2021)
The fundamental evolution mechanisms of many important phenomena accompanying explosive welding of metal foils remain a subject of open discussion, due to the extreme difficulties of in-situ observations. In this work, a comprehensive study combined SPH (smoothed particles hydrodynamics) simulation and advanced characterization was performed to investigate the interfacial evolutions, nano-mechanical properties, and the associated governing mechanisms in Cu foil/Fe welding system. Based on the simulation results, a detailed evolution model of the wave formation was given, and a new explanation for the vortex formation was proposed. The microstructure analyses revealed that the grain structures adjacent to the joining interface were dramatically changed, where two different morphologies of equiaxed and columnar grains were detected at Fe and Cu side, respectively, and the vortex area was built of ultra-fine equiaxed nanometer grains. These microstructure changes were correlated very well with the nano-mechanical properties, and the perplexing evolution processes can be explained by dynamic recovery and recrystallization accompanied by different degrees of crystal growth and deformation. The predicted widths of recrystallization layer and hardened layer agree well with the experimental results, suggesting that the SPH simulation allows predicting the microstructure evolution during the high speed impact welding process in a quantitative way.